A review of the safety of cosmetic procedures during pregnancy and lactation - M.K. Trivedi, BS, BA; G. Kroumpouzos, MD, PhD; J.E. Murase, MD (Wolters Kluwer, 2017)
The safety of cosmetic procedures in patients who are pregnant and/or lactating is a complex clinical question surrounded by uncertainty. Our objective is to consolidate data on the safety of commonly requested cosmetic procedures during pregnancy and lactation after a systematic review of the current literature to guide evidence-based care in the future. A systematic search of the PubMed database was conducted for articles on cosmetic procedures during pregnancy and lactation. Due to a lack of controlled trials, case reports and series were considered. Minor procedures such as shave, punch, snipping, and electrocautery are considered safe. With respect to chemical peels, glycolic and lactic acid peels are deemed safe; however, trichloracetic and salicylic acid peels should be avoided or used with caution. Although safety data on botulinum toxin A is insufficient, the procedure may be safe because systemic absorption and placental transfer are negligible. Sclerotherapy can be safe during pregnancy but must be avoided during the first trimester and after week 36 of the pregnancy. Laser and light therapies have been considered generally safe for patients with granulomatous conditions and condylomata. Epilation should be limited to waxing, shaving, and topical treatments instead of permanent procedures. In patients who are lactating, most therapies discussed above are safe but fat transfer, sclerotherapy, and tumescent liposuction are not recommended. Better evidence is needed to make concrete recommendations on the safety of cosmetic therapy during pregnancy and lactation but preliminary evidence suggests excellent safety profiles for many commonly requested cosmetic procedures.